Structure-activity and structure-property relationships of antimalarial pyrimido[1,2-a]benzimidazoles, imidazo[1,2-a]pyridines, and imidazo[1,2-a]pyrimidines - Alnajjar, Radwan A Sulayman (Department of Chemistry, 2024)
Malaria is an infectious disease that continues to cause significant morbidity and mortality in countries with poor infrastructure, with the African region being the most heavily affected. An estimated 241 million malaria cases were recorded in 2020, with 627,000 deaths. Of these, 77% occurred in children under the age of 5 years. Due to the widespread rise of parasite resistance, current treatments may no longer be effective. Furthermore, artemisinin-based combination treatments (ACTs), which are the first-line antimalarial medications currently recommended by the World Health Organization (WHO), are restricted in availability, prohibitively expensive, and have undesirable side effect profiles. Resistance to ACTs (albeit partial) has been reported in some Asian regions and in East Africa. Hence, there is an urgent need for new antimalarial agents with novel mechanisms of action and structural diversity. In 2011, pyrido[1,2-a]benzimidazoles (PBI) were reported as a promising novel antimalarial chemical series. However, one of the shortcomings of these compounds, which present a barrier to achieving optimal in vivo efficacy, is their poor aqueous solubility and suboptimal in vivo pharmacokinetics. In this study, the aim was to improve the physicochemical properties of previously identified PBI derivatives towards identifying new analogs able to address the aforementioned shortcomings. 1, 2 Three scaffolds were proposed based on their envisaged improved physicochemical properties, namely pyrimidino[1,2-a]benzimidazoles, imidazo[1,2-a]pyrimidines, and imidazo[1,2-a]pyrimidines. Compounds based on these scaffolds showed high in vitro antiplasmodium activity, with pyrimidino[1,2- a]benzimidazoles showing superior antiplasmodium activity and cytotoxicity profiles.